(untitled) (Comprehensive Journal of Science, 2026)
This study explores the social and economic impacts of domestic workers in the city of Zawiya, Libya—an issue that has received limited academic attention despite its growing relevance. The research focuses on the socio-economic characteristics of domestic workers, their motivations for entering the sector, and the legal and regulatory context surrounding their labor. Relying on secondary data from field studies and international reports, the study employs descriptive and statistical analysis to understand the realities of domestic labor in Zawiya. Findings reveal a dual vulnerability: economic, reflected in low wages and lack of alternatives, and legal, evident in the absence of contracts and rights awareness. The study recommends the adoption of dedicated legislation, the activation of municipal roles, and the implementation of empowerment and legal awareness programs. This research is significant due to the scarcity of local studies on the subject and the urgent need for inclusive and equitable social policy.